Integrated Network Pharmacology and Experimental Validation Approach to Investigate the Mechanisms of Stigmasterol in the Treatment of Rheumatoid Arthritis - Xie W; Yang H; Guo C; Xie R; Yu G; Li Y (Dove Medical Press, 2023)
Wendong Xie,1 Hua Yang,1 Chun Guo,2 Rui Xie,1 Guoliang Yu,1 Yifu Li1 1College of Bioscience and Biotechnology, Hunan Agricultural University, Changsha, People's Republic of China; 2Medical Innovation Experiment Center, The First Hospital of Hunan University of Traditional Chinese Medicine, Changsha, People's Republic of ChinaCorrespondence: Hua Yang, Email yhua7710@126.comBackground: Rheumatoid arthritis (RA) is a chronic inflammatory disease of the joints associated with systemic comorbidities. Sinomenium acutum is regarded as an effective traditional Chinese medicine (TCM) for the treatment of RA.Materials and Methods: Based on network pharmacology and Gene Expression Omnibus (GEO) database, 33 RA-related differentially-expressed genes (DEGs) targeting active compounds of Sinomenium acutum were initially screened in our investigation.Results: Gene Ontology (GO) and Kyoto encyclopaedia of genes and genome (KEGG) analyses found the important involvement of these DEGs in osteoclast differentiation, and finally 5 core DEGs, including NCF4, NFKB1, CYBA, IL-1β and NCF1 were determined through protein-protein interaction (PPI) network. We also identified the related active component of Sinomenium acutum include Stigmasterol. Finally, in order to experimentally verify these results, a rat model of collagen-induced arthritis (CIA) was established, and subsequently treated with Stigmasterol solution.Conclusion: Similar to the healing effect of Indomethacin, Stigmasterol was observed to reduce the levels of inflammatory factors (IL-6 and IL-1β) and osteoclast differentiation-related factors (RANKL, ACP5 and Cathepsin K), which can also reduce the arthritis index score and alleviate the degree of pathological injury of rat ankle joints. The predictions and experimental data uncover the involvement of Stigmasterol, an active component of Sinomenium acutum, in regulation of osteoclast differentiation, exerting great medicinal potential in the treatment of RA.Graphical Abstract: Keywords: rheumatoid arthritis, Sinomenium acutum, stigmasterol, network pharmacology, osteoclasts